Immunohistochemical analysis of radiation-induced non-healing dermal wounds of the head and neck - Riedel, Frank; Philipp, Katrin; Sadick, Haneen; Gößler, Ulrich; Hörmann, Karl; Verse, Thomas (In vivo, 2005)
Persistent, poorly healing wounds are a significant clinical problem in patients who have had previous irradiation. The pathology of chronic dermal ulcers is characterised by excessive proteolytic activity which degrades the extracellular matrix (required for cell migration) and growth factors and their receptors. Interestingly, the molecular basis of radiation-induced dermal wounds is poorly understood. The aim of this study was to investigate, by immunohistochemistry, the expression of the endothelial marker vWF, of angiogenic bFGF, VEGF and IL-8, of collagenases MMP-2 and MMP-9 and their inhibitors TIMP-1 and TIMP-2, in tissue samples from radiation-induced chronic dermal wounds and healthy control skin. Performing immunohistochemical detection of microvessels, an equivalent density of microvessels was observed within tissue samples from normal healthy skin and from radiation-induced non-healing cutaneous wounds. Investigation of angiogenic bFGF and VEGF demonstrated a decreased expression of both factors in the radiation-induced dermal wounds. The expression of angiogenic IL-8 was weak in both the healthy skin samples and the radiation-induced wounds. In addition, an increased expression of collagenases MMP-2 and MMP-9 protein within the radiation-induced wounds was demonstrated. While the expression of TIMP-1 showed no difference of expression between normal control skin and tissue samples from radiation-induced wounds, TIMP-2 expression was slightly increased compared to healthy controls. Our data suggest that radiation-induced dermal injuries often fail to heal because of decreased angiogenesis and persistently high concentrations of MMPs with an imbalance of their tissue inhibitors. The basic mechanisms of wound healing in radiation-induced dermal wounds at the molecular level need to be understood further for the development of innovative treatment strategies.